Biologists and the promise of American life : from Meriwether Lewis to Alfred Kinsey - Pauly, Philip J. (Princeton University Press, 2000)
"Beginning with the return of the Lewis and Clark expedition in 1806, botanists and zoologists identified science with national culture, linking their work to continental imperialism and the creation of an industrial republic. Pauly examines this nineteenth-century movement in local scientific communities with national reach: the partnership of Asa Gray and Louis Agassiz at Harvard University, the excitement of work at the Smithsonian Institution and the Geological Survey, and disputes at the Agriculture Department over the continent's future. He then describes the establishment of biology as an academic discipline in the late nineteenth century, and the retreat of life scientists from the problems of American nature